2018
DOI: 10.1002/jcp.27874
|View full text |Cite
|
Sign up to set email alerts
|

Targeting peptidylarginine deiminase reduces neutrophil extracellular trap formation and tissue injury in severe acute pancreatitis

Abstract: Recent evidence suggests that neutrophil extracellular traps (NETs) play an important role in the development of acute pancreatitis (AP). Herein, we examined the role of peptidylarginine deiminase (PAD), which has been shown to regulate NET formation, in severe AP. AP was induced by retrograde of taurocholate infusion into pancreatic duct in C57BL/6 mice. PAD was pharmacologically inhibited using Cl‐amidine, a pan‐PAD inhibitor. Pancreata were collected, and histones, citrullinated histone 3, chemokines, myelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 42 publications
1
36
0
7
Order By: Relevance
“…In addition, a recent study has shown that a cold-inducible RNA-binding protein (eCIRP), a novel damage-associated molecular pattern molecule, is present in NETs and that NET-associated eCIRP can cause tissue damage in AP [30]. Furthermore, other studies indicated that NET formation is regulated by the c-Abelson (c-Abl) kinase [31] and the histone-citrullinating enzyme peptidylarginine deiminase 4 (PAD4) in AP [32]. Knowing that the C3 activation product, C3a, exerts proinflammatory functions, we evaluated whether C3a alone can induce histone 3 citrullination and NETs formation in bone marrow-derived neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study has shown that a cold-inducible RNA-binding protein (eCIRP), a novel damage-associated molecular pattern molecule, is present in NETs and that NET-associated eCIRP can cause tissue damage in AP [30]. Furthermore, other studies indicated that NET formation is regulated by the c-Abelson (c-Abl) kinase [31] and the histone-citrullinating enzyme peptidylarginine deiminase 4 (PAD4) in AP [32]. Knowing that the C3 activation product, C3a, exerts proinflammatory functions, we evaluated whether C3a alone can induce histone 3 citrullination and NETs formation in bone marrow-derived neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…During AP, the pancreatic juice is a strong instigator of infiltrating neutrophil chromatin extrusion and thereby lead to the formation of macroscopic NETs aggregates, which may occlude pancreatic duct and drive pancreatic inflammation, inhibition of NETs formation can mitigate AP [57]. For the detection of NETs formation in AP, cell-free DNA (cfDNA) [55], MPO-DNA complex [55], or histone-DNA complex [39,75] in blood samples can be measured by commercial kits. Besides, citrullinated histone H3 (CitH3) [39,75] in pancreatic samples can be measured by western blot.…”
Section: Nets and Apmentioning
confidence: 99%
“…For the detection of NETs formation in AP, cell-free DNA (cfDNA) [55], MPO-DNA complex [55], or histone-DNA complex [39,75] in blood samples can be measured by commercial kits. Besides, citrullinated histone H3 (CitH3) [39,75] in pancreatic samples can be measured by western blot. During AP, damaged pancreatic acinar cells release proinflammatory mediators, leading to the recruitment, activation and functional changes of neutrophils and macrophages: (1) Neutrophils release proteases and ROS, which directly damage pancreatic tissue.The released MMP-9 is a potent trypsinogen activator.…”
Section: Nets and Apmentioning
confidence: 99%
See 1 more Smart Citation
“…These two NETosis pathways utilize different biochemical mediators, for example histone citrullination is a marker for the PAD4-mediated but not the ROS-mediated pathway 22,23 . Targeting PAD4 with pharmacological inhibitors is successful in inhibiting NETosis in vitro 24 and in animal models 2527 ; however, no targeted therapies for the ROS-pathway exist 2731 . DNase-1 has also been used to digest the nuclear backbone of NETs and prevent ischemia-reperfusion (I/R) injury 32 , lung injury due to cigarette smoke or mechanical ventilation 33,34 , and deep vein thrombosis 35 .…”
Section: Introductionmentioning
confidence: 99%